Effect of feeding various levels of poultry by‐product meal on the blood parameters, filet composition and structure of female tenches (Tinca tinca). (18th April 2017) - Panicz, Remigiusz; Żochowska‐Kujawska, Joanna; Sadowski, Jacek; Sobczak, Małgorzata
Abstract: Homogeneous background (age, sex, genetic lineage, culture conditions) was created to clearly demonstrate the impact of the tested dietary treatments. No feeds optimized for the rearing of the tench ( Tinca tinca L. 1758) are available. Feeds are formulated to increase the growth rate or eliminate skeletal deformations. With the increasing prices of the basic components, fish meal (FM) and fish oil, poultry by‐product meal (PBM) can be used. The aim of the study was to evaluate the effects of substitution of FM with PBM on the tench blood parameters, body composition and structure of skeletal muscles. Cage‐reared female tenches (325 ± 18 g) were fed for 86 days with five types of feeds with 0% (control), 25.7%, 48.6%, 71.4% and 100% substitution of FM with PBM. No significant differences between the formulations were reported for weight, total length, fillet weight, visceral, liver, gonado‐somatic, proximate composition and biochemical blood parameters. However, significant differences were found in the fillet profiles of fatty acids—an increase in the PBM content correlated with an increase in saturated and monounsaturated fatty acids and a decrease in n‐3 PUFA and, generally, n‐6 PUFA. Significant differences were also observed in, for example, the content of intramuscular fatty tissue and the level of organ lipidosis between the control variant (0% PBM) and that with 100% substitution. A sensory assessment indicated a higher gustatory value of the fillets in the case of feeds with 48.6% and 71.4% substitution.